The Influence of School Environment and Teacher Behavior on Teacher Professionalism in PAUD in Mesuji District - Jaenah Jaenah; Tri Widayatsih; Nila Kesumawati (International Journal of Social Science and Humanity, 2025)
This research was conducted with the aim of finding out and analyzing 1). To find out and analyze the influence of the school environment on the professionalism of teachers in PAUD in Mesuji District 2). To find out and analyze the influence of Teacher Behavior on teacher professionalism in PAUD in Mesuji District 3). To find out and analyze the influence of the school environment and teacher behavior on teacher professionalism in PAUD in Mesuji District. This study uses a quantitative method with a type of correlational research. The sample of this study was carried out in 13 PAUD in Mesuji District with a total of 44 teachers. Data collection techniques use questionnaires and documentation. The data were analyzed using correlation analysis and multiple regression techniques. The results of this study show that there is an influence of the school environment and teacher behavior together on the professionalism of PAUD teachers in Mesuji District.